2022
DOI: 10.1002/csc2.20758
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of regrowth and biomass of perennial sorghum using unoccupied aerial systems

Abstract: Perennial grain sorghum [Sorghum bicolor (L.) Moench] has potential to produce grain and forage while improving soil health, ecosystem services, and carbon soil sequestration but requires further genetic improvement. Unoccupied aerial systems (UAS, also known as drones and unmanned aerial systems) provide opportunities to quickly evaluate plant traits on a large scale with precision. Unoccupied aerial system flights were used to evaluate biomass yield and rhizome characteristics of 100 diverse sorghum hybrids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…However, we recognize many other species, from herbaceous annual crops (Grenzdörffer, 2019) all the way up to perennial trees (López‐Granados et al., 2019), are using UAS tools to enhance their small‐plot research and breeding. Forage grasses and silage provide an especially interesting case to look at breeding for the aboveground biomass throughout the season (Alvarez‐Mendoza et al., 2022; de Oliveira et al., 2021; Nakasagga et al., 2022), while cassava ( Manihot esculenta Crantz), peanut ( Arachis hypogaea ), and potato ( Solanum tuberosum L.) UAS research (de Jesus Colwell et al., 2021; Sarkar et al., 2021; Selvaraj et al., 2020) has shown that below ground biomass yield can be estimated from UAS. Each of these species had to develop a unique methodology.…”
Section: Discussionmentioning
confidence: 99%
“…However, we recognize many other species, from herbaceous annual crops (Grenzdörffer, 2019) all the way up to perennial trees (López‐Granados et al., 2019), are using UAS tools to enhance their small‐plot research and breeding. Forage grasses and silage provide an especially interesting case to look at breeding for the aboveground biomass throughout the season (Alvarez‐Mendoza et al., 2022; de Oliveira et al., 2021; Nakasagga et al., 2022), while cassava ( Manihot esculenta Crantz), peanut ( Arachis hypogaea ), and potato ( Solanum tuberosum L.) UAS research (de Jesus Colwell et al., 2021; Sarkar et al., 2021; Selvaraj et al., 2020) has shown that below ground biomass yield can be estimated from UAS. Each of these species had to develop a unique methodology.…”
Section: Discussionmentioning
confidence: 99%